Peningkatan Motivasil Belajar Mahasiswa Prodi PGSD Universitas Trilogi Jakarta dengan Media Flash Card and Asking and Giving Question Method Pada Mata Kuliah Belajar dan Pembelajaran - Satriyani, Febrianti Yuli (Penerbit STKIP PGRI Bangkalan, 2019)
Learning motivation plays an important role in learning activities, which makes students feel excited in learning activities so they can produce good learning outcomes. During this time the learning activities in PGSD Study Program are still dominantly done conventionally with lecturers as the main actors in lecture activities. From the results of observations and interviews, data were obtained that students preferred student centered based learning and they were actively involved in learning activities. This study aims to describe, (1) the implementation of learning by using flash cards and asking and giving question methods in learning and learning courses in first semester students of the Primary teacher education study program University Trilogy Study Program, and (2) the effect of implementing learning using flash card media and asking and giving question method on learning and learning courses in first semester students of PGSD University Study Program Trilogy towards increasing student learning motivation.                The approach used in this study is qualitative research with a type of classroom action research. Data collection techniques are carried out by observation, interviews, and documentation. The data analysis technique used is descriptive qualitative using the Kemmis and Taggart models which include: (1) planning, (2) implementation of actions, (3) observation (observation), and (4) reflection.                The results of the study show that the application of Flash Card Media and Asking and Giving Question Methods in Learning and Learning Courses can increase students' learning motivation. They all seemed to actively construct their own knowledge, through meaningful learning activities by contributing students in making questions and answers to the flash card and then randomly making a asking and giving question to their classmates. The learning atmosphere looks active, students look enthusiastic in learning activities. Suggestions based on this research are to disseminate ways to make flash card media and improve the assessment method in applying asking and giving question activities. Keywords: Motivation to learn, Flash Card, Asking and Giving Question.